Czy chrześcijanin musi być kreacjonistą młodej Ziemi? - Chaberek, Michał (Collectanea Theologica, 2018)
This paper answers the question of whether or not a Christian has to be a Young Earth creationist. The article opens with the typology of the current positions in the creation-evolution debate. Basing itself on this typology, it presents Young Earth creationism as one of four positions, the only one that denies the concept of “deep time”. Next, the paper presents the genesis of Young Earth creationism in Western thought. In the third part there is a brief response to the argument of the proponents of a Young Earth that early Christianity supported the young age of the universe. In the following part it is explained that Young Earth creationism confuses the scientific with the theological statements. At the end, a document of the Catholic Church is presented which explains that Catholics can understand the “day” in the creation account as either a natural day or any other period of time. This makes room for other positions within Catholic orthodoxy apart from that of a Young Earth.